Evolution of the Arabic knowledge about western and central Sūdãn The region’s information in the Arab geographical works until the end of the (4AH/10AD) century - mohamed, Krim (The Algerian Historical Journal, 2026)
Knowledge about a geographical field is formed as a result of a group of factors, the most important of it is eye-witness, or reporting the news through what others declared, or accumulating hearing, Gradually, images about this geographical area are formed in the person’s imagination, It becomes more clear, and perhaps becomes confused and unclear, there is no doubt that distant geographical areas, such as those located south of the desert and known as the countries of Sūdãn, began to witness an increasing presence in Arab geographical works, which controlled the image of this region in the Arab imagination in the medieval era .This article examines the mechanisms of reporting the news and the type of knowledge achieved in these areas until the end of the fourth century AH (10AD).